La incidencia de la fiscalidad de la monarquía en el territorio riojano durante el reinado de los Reyes Católicos. Notas sobre la recaudación de las Alcabalas - Diago Hernando, Máximo (En la España Medieval, 2007)
A study of the way the fiscal machinery of the Castilian monarchy operated in the Rioja region during the last decades of the fifteenth century and the first decades of the sixteenth, paying particular attention to the analysis of the procedures of collection of an indirect tax called the “alcabala”. After a short description of the division of the territory of the Rioja in fiscal districts, the author describes the practice of collection of the product of the “alcabalas” by the members of the nobility in their lordships. He then considers the returns of the tax in the remaining places where the monarchy received its product, and, finally, offers notes about the way the tax was collected in the main urban centres.